A rapid appraisal of the status of the Antitretroviral Programme in facilities where roll out has started and those where roll out is planned in Gauteng Province - Central Wits Region - Nxumalo, Nonhlanhla Lynette (My University, 2006)
When the South African government decided to implement the roll out of antiretrovirals (ARVs) in public health facilities, as part of its HIV/AIDS care and treatment plan, there was concern about the capacity of the country’s health care system, to deliver the service efficiently and equitably. The study was deemed necessary, due to that the South African government requires information and feedback on the state of its health care system to provide ARVs in public health facilities. The study will add to the growing body of knowledge on the status of the ARV programme and therefore assist in the improvement of the efficiency and efficacy of the services. The objective of this study was to conduct a rapid appraisal of the status of roll out of the ARVs in facilities that had begun offering the service and the readiness of facilities that were planning to roll out, in the Gauteng Province. Focus was on the capacity of these facilities to provide the ARV services, as outlined by the Provincial Department of Health. It is a descriptive cross- sectional study, drawing on qualitative methods such as thematic analysis, document review and a facility checklist. A sample was determined by purposely selecting participants who were involved in the ARV programme. Participants included facility managers, doctors and nurses from the study facilities, regional managers and representatives from non-profit organisations. Perspectives about the roll out were drawn from in-depth interviews from 27 participants, including document reviews and a facility checklist. The study highlighted the fact that the ARV programme is implemented within a health care system that is experiencing weaknesses and bottleneck problems in the following facets: human resources, training, referral systems, management and monitoring and evaluation systems. Findings indicated that the core weaknesses and constraints in the implementation of ARVs are systemic and hence will require intervention at a systemic level. It is recommended that the Department of Health improve the recruitment and retaining of health professionals, improve training and training structures, improve communication channels and support systems, provide skills to local government, managers and improve monitoring and evaluation systems.
Student Number : 9206687V - Master of Public Health research report - School of Public Health - Faculty of Health Sciences